2016
DOI: 10.1037/pas0000141
|View full text |Cite
|
Sign up to set email alerts
|

Initial development of a treatment adherence measure for cognitive–behavioral therapy for child anxiety.

Abstract: The measurement of treatment adherence (a component of treatment integrity defined as the extent to which a treatment is delivered as intended) is a critical element in treatment evaluation research. This paper presents initial psychometric data for scores on the Cognitive-Behavioral Therapy Adherence Scale for Youth Anxiety (CBAY-A), an observational measure designed to be sensitive to common practice elements found in individual cognitive-behavioral therapy (ICBT) for youth anxiety. Therapy sessions (N = 954… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(44 citation statements)
references
References 34 publications
2
42
0
Order By: Relevance
“…A coder considers both thoroughness and frequency while making a rating; extensiveness ratings thus provide dosage information about each intervention. Previous studies have demonstrated that the TPOCS-RS, or variants thereof (i.e., PRAC-TPOCS, Garland et al, 2010; TPOCS-S, McLeod & Weisz, 2010), have demonstrated item inter-rater reliability ranging from .71 to .86 ( M ICC = .81), the item and subscale scores provide evidence of construct validity across research and practice settings (McLeod & Weisz, 2010; McLeod et al, 2015; Southam-Gerow et al, 2016; Wood et al, 2006), subscales scores differentiate between treatment types (McLeod et al, 2015; Southam-Gerow et al, 2010; Weisz et al, 2009; Wood et al, 2006), and subscale scores demonstrated predictive validity (Garland et al, 2014). The current study used the TPOCS-RS Psychodynamic, Family, and Client-centered subscales.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A coder considers both thoroughness and frequency while making a rating; extensiveness ratings thus provide dosage information about each intervention. Previous studies have demonstrated that the TPOCS-RS, or variants thereof (i.e., PRAC-TPOCS, Garland et al, 2010; TPOCS-S, McLeod & Weisz, 2010), have demonstrated item inter-rater reliability ranging from .71 to .86 ( M ICC = .81), the item and subscale scores provide evidence of construct validity across research and practice settings (McLeod & Weisz, 2010; McLeod et al, 2015; Southam-Gerow et al, 2016; Wood et al, 2006), subscales scores differentiate between treatment types (McLeod et al, 2015; Southam-Gerow et al, 2010; Weisz et al, 2009; Wood et al, 2006), and subscale scores demonstrated predictive validity (Garland et al, 2014). The current study used the TPOCS-RS Psychodynamic, Family, and Client-centered subscales.…”
Section: Methodsmentioning
confidence: 99%
“…Without consensus on how to score integrity instruments (see McLeod et al, 2015; Southam-Gerow et al, 2016), we considered three approaches: (a) Average of all items on each subscale for each session (Coping Cat M = 2.63, SD = 1.22; Psychodynamic M = 1.19, SD = 0.35; Family M = 1.57, SD = 0.85; Client-Centered M = 2.76, SD = 0.76); (b) Average of all scored items (items scored above a 1) for each session (Coping Cat M = 3.08, SD = 1.22; Psychodynamic M = 1.40, SD = 0.60; Family M = 1.96, SD = 1.14; Client-Centered M = 3.11, SD = 0.79); and (c) Highest item scored for each session (Coping Cat M = 4.56, SD = 2.10; Psychodynamic M = 1.49, SD = 0.81; Family M = 2.52, SD = 1.91; Client-Centered M = 4.28, SD = 1.41). Though scores on the three scoring approaches differed in magnitude, the three scores for each subscale were highly correlated (all r s > .78).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, weincluded items that assesscompetence in delivering interventions common to many CBT approaches (e.g., homework assignment;Stallard et al, 2014). Second, and consistent with most competence instruments (Bjaastad et al, 2015; Forgatch et al, 2005; Gutermann et al, 2014; Hogue et al, 2008a), wedeveloped items that gaugecompetence in delivering the core theory-driven interventions central to ICBTfor youth anxiety (e.g., coping plan, exposure).Third, we developed items that measurecompetence in specific delivery methods (e.g., didactically or via rehearsal; Southam-Gerow et al, 2016), an approach found in a previous competence instrument (Forgatch et al, 2005). …”
mentioning
confidence: 99%
“…Indeed, an active therapist can implement one or two interventions very thoroughly during a given session yet still receive a below-midpoint mean adherence score that has been averaged across multiple scale items. Another metric for judging the density of EBT delivery in usual care might be tabulating the proportion of sessions in which one (or a few) discrete techniques are scored at or above the midpoint value, indicating the presence of considerable/extensive EBT activity (e.g., Southam-Gerow et al, 2016); though beyond the scope of the current study, analyses of this kind would further enrich our understanding of UC treatment processes (Hurlburt et al, 2010). …”
Section: Discussionmentioning
confidence: 99%